Implementation Of The Principles Of Transparency To Ensure Legal Protection For Sharia Bank Customers In Indonesia - Pelengkahu, Muhammad Rahjay (Jurnal Panorama Hukum, 2022)
This study's objective is to investigate the implementation of the principle of transparency in Sharia banking operations to guarantee legal protection for Islamic bank customers. This study utilised descriptive analysis as its research approach. Secondary data, including laws and regulations, papers, books, research reports, and other sources or information pertinent to this subject, are employed. Then, the method of data collection is library research or library research. The study's findings indicate that transparency is one of the most crucial parts of implementing excellent corporate governance. Article 34, paragraph (1) of the Law of the Republic of Indonesia Number 21 of 2008 concerning Islamic Banking regulates the principle of transparency. This paper's case studies and discussion demonstrate that transparency and Good Corporate Governance can provide the best protection for customers. Hence the principle of transparency must be adopted. as a sort of legal protection for sharia bank consumers in sharia banking activities.